Fungsi Penegakan Hukum Pidana Terkait Tanggungjawab Diskresi Kepolisian - Zulkifli Zulkifli (Universitas Jayabaya, 2020)
This study aims to see that police discretion has the potential to be abused, in justice, acts of corruption are things that cannot be hidden anymore. Pretrial as a means of control and supervision in its implementation has limitations. Based on the result, police discretion liability in the function of criminal law enforcement in Law on Police and Criminal Procedural Code was not governed expressly. Therefore, the concept of police discretion must obtain clearer, more measured, and objective interpretation and explanation so that the legitimization and operational are application and in line with the conception of legal state, law enforcement, and law liability. The absence of mechanism and examining and/or testing institution could not be maintained anymore, so had to be open to the obligation to account for it, either by pseudo-administrative trial, pure administrative trial, or both, with internal liability or external liability. Besides that, the aspect of legitimization and operational of police discretion was not applicable, limited by and in the sense within the scope of its legality principle and specification, and could not be used in the function of criminal law enforcement except police investigator discretion as a form of special discretion and constituted a specification of police discretion, realized in free discretion and bound discretion according to the Criminal Procedural Code.